2022
DOI: 10.3390/su141711102
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Rapeseed Green Manure and Its Effect on Soil under Two Residue Return Levels

Abstract: The overuse of chemical fertilizers has caused various ecological problems in China, necessitating the development of organic alternative fertilizers. There are few studies on the rapidly emerging organic fertilizer rapeseed green manure, despite the importance of understanding its decomposition efficiency and impact on soil. In this study, using plant residue from 14 rapeseed cultivars, we examined the 30-day decomposition changes under conditions A and B (150 and 300 g of plant residue returned, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The soil nutrient boosting effect of HV and OV was the most significant during the period from straw return to the V3 stage of maize when compared to Fallow and Wheat. It was estimated that more than 50% of fresh green manure could decompose within 30 days (Meena et al., 2018; Wang et al., 2022). The mineral nutrients could be absorbed by maize seedlings or quickly leached by abundant rainfall in July (190 mm).…”
Section: Discussionmentioning
confidence: 99%
“…The soil nutrient boosting effect of HV and OV was the most significant during the period from straw return to the V3 stage of maize when compared to Fallow and Wheat. It was estimated that more than 50% of fresh green manure could decompose within 30 days (Meena et al., 2018; Wang et al., 2022). The mineral nutrients could be absorbed by maize seedlings or quickly leached by abundant rainfall in July (190 mm).…”
Section: Discussionmentioning
confidence: 99%
“…During the vetch growing season, maximum P uptake by vetch (Anugroho et al, 2009b) might have caused a decrease in soil TP (Figure 2C), which further led to microbial P limitation (Figure 4B). Subsequently, during vetch decomposition, microbes benefitted from the P released from vetch (Wang, Ma, et al, 2022) and increased soil TP (Figure 2C), thus reducing microbial P limitation (Figure 4B). However, the rapid mineralization of legumes may accelerate N cycling and ultimately lead to soil N deficiency during the decomposition season (Gaskell & Smith, 2007; Watthier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, during vetch decomposition, microbes benefitted from the P released from vetch (Wang, Ma, et al, 2022) and increased soil TP (Figure 2C), thus reducing microbial P limitation (Figure 4B). However, the rapid mineralization of legumes may accelerate N cycling and ultimately lead to soil N deficiency during the decomposition season (Gaskell & Smith, 2007;Watthier et al, 2019).…”
Section: Relationship Among Microbial Metabolic Limitation Root- and ...mentioning
confidence: 99%
“…Soil microhabitat (such as soil type, soil pH, soil nutrient content, and soil microbial activity) also signi cant effect on green manure decomposition (Watthier et al 2020; Carrasco-Barea et al 2022). The relatively higher enzyme activities found in the mature rubber plantation (Table 1), favor microbial activity and contribute to kudzu decomposition (Wang et al 2022). This is consistent with the results of Ye et al (2014) who indicated that soil microorganisms together with soil enzymes promote the transformation and cycle of various organic matter residues that lets the soil keep normal metabolic functions.…”
Section: Factors Kudzu Decompositionmentioning
confidence: 99%